THE USE OF INNOVATIVE TECHNOLOGIES IN THE SYSTEM OF DISTANCE LEARNING IN UNIVERSITIES - Xolbekova Matluba Abdufattoyevna; Xolbekov Sherzod Rasuljonovich (American Journals Publishing, 2024)
The article discusses the use of innovative technologies in the distance learning system in universities".
Keywords: Education, activity, training, expert, pedagogy, distance learning, model, personalization, functions, process, to test.